Video consultation for new colorectal patients. (31st July 2020) - Sellars, H.; Ramsay, G.; Sunny, A.; Gunner, C. K.; Oliphant, R.; Watson, A. J. M.
Abstract: Aim: For patients, an outpatient review can lead to a stressful journey to hospital with the resultant risks associated with breaching social distancing. Despite this, video consultations (VCs) have not been frequently used in colorectal practice. We assessed outcomes, including the economic and environmental impact, of a VC clinic for new colorectal referrals. Method: This was a prospective observational study. Fifty consecutive patients attending a VC colorectal appointment were reviewed between March 2019 and February 2020. Face‐to‐face appointments during the same time period were also assessed. The distance, time, cost and carbon emissions of journeys were estimated using web‐based resources. Estimated loss of earnings used data from the Office for National Statistics. The subsequent management plans were also recorded. Results: Of 50 patients using VC, 40 used home devices and 10 used equipment in their local medical facility. Three patients had difficulties with the technology and converted to telephone review. Failure to attend VC appointments was less than for face‐to‐face appointments (4% vs 6.1%). VC appointments saved 6685 miles of travel (range 2–364 miles), 148 h travelling time and £1767 costs. Additional savings for loss of earnings were approximately £33.56 per patient. The carbon emissions saved was 4659 lb CO2 equivalent, corresponding to over 250 000 charges of a smartphone. Conclusion: The use of VC resulted in significant savings related to travel and reduced time and costs for patients who chose to use the service, in addition to the environmental benefits. In this current climate VC clinics have a central role in outpatient care for both new patients and follow‐ups.